Maria Ulfah sebagai Pelopor Hak Perempuan dalam Undang-Undang Perkawinan di Indonesia - Intan, Mawar Dwy; Umamah, Nurul; Hilmiah, Anis Syatul (Neolectura, 2024)
This article analyzes Maria Ulfah's significant role in pushing for the protection of women's rights in Indonesia's marriage laws. As an influential women's activist, Maria Ulfah played a key role in formulating and advocating for laws that recognized women's rights in the context of marriage. Her contribution to changing the paradigm of marriage law from one that tended to disadvantage women to one that was more inclusive and fair is analyzed. Using a historical and contextual approach, this article highlights Ulfah's participation in bringing about positive change for women in Indonesia's marriage law system. The study uses qualitative research methods with a historical approach and document analysis to investigate Maria Ulfah's role and contribution. The article also examines the challenges faced during the legislative process as well as the impact of the changes to the marriage law on the lives of Indonesian women. The findings show that these legislative changes have improved legal protection, access to economic rights, as well as a social paradigm shift that is more respectful of gender equality. This research emphasizes the importance of continuous advocacy to achieve gender equality in the Indonesian legal